Desenvolvimento da aveia branca e disponibilidade de fósforo em razão da aplicação de silicato de potássio - Garcia, Rodrigo Arroyo; Merlin, Alexandre [UNESP]; Toledo, Mariana Zampar; Fernandes, Dirceu Maximino [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Büll, Leonardo Theodoro [UNESP] (My University, 2012)
Potassium silicate application in soil can increase phosphorus availability and influence white oat growth. This work had the objective of evaluating the effects of silicate doses applied to the soil on the white oat growth and on soil P availability. The experimental design was completely randomized, with six replications, analyzed as a 2 × 4 factorial. Treatments consisted of two P doses (20 and 200 mg dm-3 of P2O5) combined with four Si doses (0, 150, 300 and 450 mg dm-3), applied at sowing. Dry matter of leaves+stems, panicles and total shoot were evaluated right after harvest. P and Si contents were evaluated in grains and panicle straw, previously separated, as well as in leaves+stems. Concentrations of Si and P in soil after harvest were also determined. Fertilization with potassium silicate increases Si levels in soil and increases P availability. Dry matter of leaves+stems is increased by silicate whenever initial P levels are low. Even considering the highest P dose, silicate application increases P availability in soil, and the plant P uptake. Si contents in panicle straw, leaves+stems and grains are influenced by the higher availability of this element in soil.
White oat development and phosphorus availability affected by potassium silicate application
Keywords: Avena sativa; Phosphate.; Silicon